Analysis of Intrinsic Elements, Psychological Approach, and Character Value through the Novel “A Monster Calls” - Aryatama, I Wayan Eca (STKIP Agama Hindu Singaraja, 2023)
This study aims to analyze the Intrinsic Elements, Psychological Approach, and Character Values in the novel entitled “A Monster Calls” by Patrick Ness using psychological analysis and its association with character values. This research uses library research method. The data in this study were analyzed using qualitative or descriptive methods. Data collected from the main source directly. The results of this study indicate that there are several components contained in the intrinsic and psychological elements associated with the main character in this novel, namely the main character, setting, plot, and point of view. There are three types of character values that can be analyzed, namely religious, honest, and hard-working.